Basement-involved, shallow detachment faulting in the Bighorn Basin, Wyoming and Montana. (March 2019) - Gray, Gary; Zhang, Zuyue; Barrios, Andres
Abstract: 'Laramide-style' structures from the Laramide province of the western US involve the underlying crystalline basement. The basement is broken into blocks of varying scales that are generally bounded by moderately-to-steeply dipping reverse faults. This style is very pervasive, so that most structures are interpreted this way, even when field relationships suggest otherwise. The Elk Basin anticline, which lies in the northern Bighorn Basin is one of these structures. Basement is not elevated on the southwest side of the structure, however, which argues strongly for a detached origin. Balanced section restoration and forward finite-element modeling both support the interpretation that the underlying Elk Basin thrust is a detached, listric or ramp-flat style thrust fault. The detachment lies within the crystalline basement, ∼0.5 km below the sediment-basement contact. This detachment is fundamentally different from the detachments in the deep crust interpreted by Erslev (1993) to be the underlying link between widely-separated basement arches within the Laramide province. We propose a new 'shallow basement detached' class of structural style. Several candidate structures for this same style are present within the Bighorn basin, with both east and west vergence. These structures do not appear to form an interconnected detachment system, but rather are local 'flakes' of basement that may form due to bending of the underlying crust during basin-scale Laramide-age contraction and folding. Highlights: A new type of shallow detachment structure is recognized that involves crystalline basement. The detachment is approximately 2.2–2.4 km below the basement sediment contact. This structure is found where only steeply-dipping basement faults had been believed to exist. There are other examples like this detached structure that may have been mis-interpreted. These detachments probably form due to large-scale bending of the basement.